The Combination of Aquilaria sinensis (Lour.) Gilg and Aucklandia costus Falc. Volatile Oils Exerts Antidepressant Effects in a CUMS-Induced Rat Model by Regulating the HPA Axis and Levels of Neurotransmitters - Huiting Li; Yuanhui Li; Xiaofei Zhang; Guilin Ren; Liangfeng Wang; Jianzhe Li; Mengxue Wang; Tao Ren; Yi Zhao; Ming Yang; Ming Yang; Xiaoying Huang (Frontiers Media S.A., 2021)
The Aquilaria sinensis (Lour.) Gilg (CX)-Aucklandia costus Falc. (MX) herbal pair is frequently used in traditional Chinese medicine prescriptions for treating depression. The volatile oil from CX and MX has been shown to have good pharmacological activities on the central nervous system, but its curative effect and mechanism in the treatment of depression are unclear. Therefore, the antidepressant effect of the volatile oil from CX-MX (CMVO) was studied in chronic unpredictable mild stress (CUMS) rats. The suppressive effects of CMVO (25, 50, 100 μL/kg) against CUMS-induced depression-like behavior were evaluated using the forced swimming test (FST), open field test (OFT) and sucrose preference test (SPT). The results showed that CMVO exhibited an antidepressant effect, reversed the decreased sugar preference in the SPT and prolongation of immobility time in the FST induced by CUMS, increased the average speed, time to enter the central area, total moving distance, and enhanced the willingness of rats to explore the environment in the OFT. Inhalational administration of CMVO decreased levels of adrenocorticotropic hormone and corticosterone in serum and the expression of corticotropin-releasing hormone mRNA in the hypothalamus, which indicated regulation of over-activation of the hypothalamic-pituitary-adrenal (HPA) axis. In addition, CMVO restored levels of 5-hydroxytryptamine (5-HT), dopamine, norepinephrine and acetylcholine in the hippocampus. The RT-PCR and immunohistochemistry results showed that CMVO up-regulated the expression of 5-HT1A mRNA. This study demonstrated the antidepressant effect of CMVO in CUMS rats, which was possibly mediated via modulation of monoamine and cholinergic neurotransmitters and regulation of the HPA axis.